ANTIPROLIFERATIVE AND APOPTOGENIC EFFICACY OF ANTIDIABETIC DRUGS METFORMIN AND SITAGLIPTIN AGAINST MCF7 AND HEPG2 CANCER CELLS: A COMPARATIVE MOLECULAR STUDY - Sarkar, Mrinmoy; Dey, Sananda; Giri, Biplab (Journal of Drug Delivery and Therapeutics, 2017)
Lifestyle and diet-related disorder type 2 diabetes (T2D), has reached epidemic margin globally. The relationships between diabetes and cancer are complex. However, evidence supports the hypothesis that obesity raises the risks of both T2D and certain cancers. A further complication arises from the controversy that drugs used in the treatment of T2D increase or decrease cancer risk or influence cancer diagnosis. Herein, we hypothesized that the antidiabetic medications can improve cancer outcome. In this study, we have studied the potency and efficacy of two well-known antidiabetic drugs metformin and sitagliptin. Although there are controversies for the usage of DDP4 inhibitors, we found that sitagliptin has a potent cytotoxic effect on both type of cancer cells (MCF7 and HepG2). It has also shown certain impact on early apoptogenic efficacy in HepG2 and late apoptogenic efficacy on MCF7 as well as the caspase-3 activity expression in both cell lines. In the line of our study, it might be concluded that sitagliptin has significant antiproliferative and apoptogenic efficacy in MCF7 and HepG2 cancer cells, though it was observed to be lesser than that of metformin. Further thorough investigation in a cancer-diabetes animal model, as well as the trial on cancer-diabetic human subjects, is required to establish the efficacy of type 2 antidiabetic drugs in treating diabetic cancer patients. Keywords: Metformin; Sitagliptin; DPP4 inhibitor; Cancer; Diabetes; Proliferation; Â Apoptosis;